An explicit approach to the Baum-Connes conjecture for some semi-direct products - Pooya, Sanaz (My University, 2018)
On investigue la conjecture de Baum-Connes pour quelque exemples concrets. Cette conjecture est vraie pour plusieurs classes des groupes, en particulier les groupes a-T-moyennables, grâce au travail de Higson-Kasparov. En faisant référence à ce résultat on n’obtient qu’un isomorphisme abstrait. Dans cette thèse on décrira explicitement le morphisme d’assemblage des groupes a-Tmoyennables; BS(1, n) où n > 1 et F≀𝔽n où F est fini et n ≥ 1. Tous ces groupes peuvent être écrits comme un produit semidirect. Cette approche explicite, naturellement, contient calculs de K-theórie et K-homologie équivariante, celle-ci étant reliée à l’homologie de Bredon. Notre outil pour les calculs en K-théorie est la suite exacte à 6-termes de Pimsner-Voiculescu et pour calculer la K-homologie équivariante, on exploite les suites spectrales d’Atiyah-Hirzebruch et de Lyndon-Hochschild-Serre. Pour avoir une image claire et complète de la conjecture dans ces cas, on ajoute la description des modèles concrets d’espaces classifiants. En plus, on présente des bases naturelles de K-groupes et on les identifie par le morphisme d’assemblage. En faisant cela, on redémontre la conjecture de Baum-Connes pour ces groupes. Finalement, en considérant la conjecture de la trace modifiée, on calcule directement l’image de la trace induite., We investigate the Baum-Connes assembly map through concrete examples. It is known that the Baum-Connes conjecture holds for large classes of groups including a-T-menable groups, thanks to work of Higson and Kasparov. However neither of these works describes the K-groups. In this thesis we describe explicitly the Baum-Connes assembly map for some a-T-menable groups namely BS(1, n), where n > 1 and F≀𝔽n, where n ≥ 1 and F is a finite group. Our explicit approach by nature involves computations of K-theory and equivariant K-homology with the latter being tightly related to Bredon homology. Our main tools to compute the K-theory is the Pimsner-Voiculescu 6-term exact sequence and to compute the equivariant K-homology we employ spectral sequences, namely suitable versions of Atiyah-Hirzebruch and Lyndon-Hochschild-Serre. In order to provide a complete and clear picture of the conjecture for these groups, we include concrete models for their classifying spaces. Moreover, we present natural sets of generators for the K-groups and identify them via the assembly map. In doing so, we reprove the Baum-Connes conjecture for these groups. Finally, in the context of the (modified) trace conjecture, we directly calculate the image of the induced trace and verify that this is the desired subring of ℝ.
Thèse de doctorat : Université de Neuchâtel, 2018
Keywords: La conjecture de Baum-Connes; K-théorie; K-homologie équivariante; l’homologie de Bredon; la conjecture de la trace modifiée; The Baum-Connes conjecture; wreath product; K-theory; equivariant K-homology; Bredon homology; the modified trace conjecture